Comparative Analysis of Three Technology Companies - WEN, TEY BO (Transactions on Economics, Business and Management Research, 2024)
Three of the top tech companies—Apple, Tesla, and Lenovo—are carefully examined financially in this essay. These three businesses are also involved in various sectors of the technology sector. Apple is in the software and hardware business, Tesla is in the electric vehicle business, and Lenovo is in the computer business. The purpose of this study is to offer professional and insightful information on these three firms’ successful investment strategies. This study includes a review of these firms’ most current financial indicators, including an examination of the significance of various data points, as well as a study of the difficulties that different investor types—such as Value, Income, PEG, Index, and Momentum investors—face when choosing assets. Additionally, this research has shown that different investor types are open to purchasing different kinds of equities. Furthermore, value investors tend not to purchase the stocks of all three firms. The analysis’s conclusions aid in the creation of precisely customized investment plans, which ultimately seek to maximize financial benefits in the tech sector.